Persepsi mahasiswa akuntansi mengenai keadilan,sistem perpajakan dan diskriminasi atas penggelapan pajak (tax evasion) - Mukoffi, Ahmad Mukoffi; Indrihastuti, Poppy; Himawan Wibisono, Sukarno; Selni, Rosvita Selni (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
The purpose of this study is to find out the influence of justice, tax systems and discrimination against ethics over tax evasion. Case study at the Faculty of Economics, class of 2018, Tribhuwana Tunggadewi University. This research technique is quantitative. The sample collection technique in this study used incidental sampling techniques with a sample number of 37 accounting student respondents whose class of 2018 had taken taxation courses. The data collection method is carried out using questionnaires distributed to respondents through google forms then using SPSS statistics 26. As a result of this study, the element of fairness has a significant effect on ethics for tax evasion. The components of the tax system have a significant effect on ethics over tax evasion. The Discrimination component has a significant effect on ethics for tax evasion.